Modulating the Activity of MPFC With tDCS Alters Endowment Effect - Guo, Wenmin; Shi, Jinchuan; Lu, Xinbo; Ye, Hang; Luo, Jun (Frontiers in Behavioral Neuroscience, 2019)
Endowment effect—the observation that people appear to attach more value to possessions than non-possessions—has been replicated in numerous experimental studies. Previous neuroimaging studies revealed that the medial prefrontal cortex (MPFC) plays a role in the endowment effect. To assess the possibility of a direct causal relationship between the activity of MPFC and the endowment effect, we used transcranial direct current stimulation (tDCS) to transiently alter the neural activity in MPFC. Subsequently, in three stimulation treatments, we assessed the presence of the endowment effect, which was demonstrated by a disparity between willingness to accept (WTA) and willingness to pay (WTP). The results indicated that the participants demonstrated the endowment effect for a mug in the anodal and sham treatments, whereas no endowment effect was observed in the cathodal treatment. Similarly, endowment effect was observed for the other item (notebook) in the anodal treatment, whereas no endowment effect was observed in the sham and cathodal treatments. In addition, the participants tended to sell higher and buy lower after receiving anodal tDCS over MPFC and buy higher after receiving cathodal tDCS over MPFC. As a result, the present study demonstrated a direct causal relationship between the activity of MPFC and the endowment effect.